A convenient synthesis of NiO-CuS/molecularly imprinted polymer nanocomposites with highly enhanced adsorption activity and selectivity for removal of Letrozole. Issue 6 (12th April 2020) - Rabizadeh, Hanieh; Feizbakhsh, Alireza; Panahi, Homayon Ahmad; Konoz, Elaheh
ABSTRACT: In this study, Novel NiO-CuS nanocomposites were prepared by simple chemical method. The goal of this project was to apply the Letrozole (Anti-estrogen drug) template molecularly imprinted polymer (MIP) for the selective removal of Letrozole from aqueous samples. The NiO-CuS nanocomposites and NiO-CuS/MIP nanocomposites were specified by field emission scanning electron microscopy, X-ray diffraction, photoelectron spectroscopy, N2 adsorption-desorption, and thermogravimetric analysis. The performance of the NiO-CuS and NiO-CuS/MIP nanocomposites was analyzed by optimizing various removal factors. The optimized data for adsorption process were 0.01 g/L: MIP, contact time: 40 min and pH: 7.0. The data was evaluated best by pseudo 1st and 2nd order equation which revealed a chemical adsorption of letrozole onto NiO-CuS and NiO-CuS/MIP particles, respectively. The result of R 2 values indicated that the adsorption data followed the Langmuir isotherm equation which defined that the binding agent happened on the homogeneous sites of adsorbent.